ECOLOGY TUTORING AS PART OF TECHNOLOGY MODULE IN PRE - SCHOOL EDUCATION - PYTEL, Krzysztof (Trends in education, 2009)
State of getting worst of natural environment appears with ecological and economical crisis that causes difficulties and general feeling of threat. The education of society, first of all realized among children and youth becomes very important to understand this situation. The process of education as well as formation of values in human being are very important aspects of peoples life, that can be to hold in educational places or outside of them. Ecological consciousness assimilated by young man is folded notion. Ecological consciousness can be individual and can be social, in depend on fact, if introduces individually or universally assessment. Both these consciousnesses possess feasible assessment, because there is a really existing consciousness in society, and one can verify its level. The qualification of role of ecology education in area of teaching is realized in integrated pre - school education and this is the aim of conducted analyses. The education takes a course in field of content of supporting children's intellectual development by constructional parties in order to get up technical interests.
Keywords: IT; techniques; didactics; ecology.